Making Sense and Drawing Lines: Young adults and the mixing of news and entertainment. (3rd August 2017) - Edgerly, Stephanie
Abstract : This study takes a closer look at the blurring of news and entertainment by examining how a sample of media users talk about various sources of current events information. Data from 21 in-depth interviews with young adults indicate that young adults do not hold a single notion of news and its relationship to entertainment. Rather, they draw from a variety of cultural resources at their disposal to either oppose or welcome the mixing of news and entertainment. A typology is developed to describe four distinct outlooks interviewees hold toward the value of news and whether it should be distinguished from entertainment.